FORMULATING THE IMPLEMENTATION OF MUQASAH IN MURABAHAH FINANCING IN INDONESIA’S ISLAMIC BANK - Ahmad Fajri Prabowo; Oktofa Yudha Sudrajad (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
In Islamic banking in Indonesia, murabahah (contract of trading) is one of the most popular contracts to use in the financing products. In order to regulate this contract, Indonesia’s Otoritas Jasa Keuangan (OJK) issued the Guidance on Murabahah Financing which comprehensively stipulate the rules in distributing the financing under the contract of murabahah. One of the stipulations in the Guidance governs the mandatory discount for the early-settled financing, later referred to as the muqasah. This research highlighted the potential impact of implementing the regulation in the Bright Bank, a listed sharia Bank which distributes majority of its financing under the contract of murabahah. Both quantitative and qualitative studies were conducted to understand the financial magnitude of the implementation of muqasah in the Bright Bank, to formulate the potential financial scheme (i.e. early-settlement fee) that will prevent further loss on the bank’s profitability, and to understand the customers’ perception on early financing settlement and the prospectively implemented surcharge. The solution offered in this writing is a policy-based strategy that is based on the research result. This research will contribute to be one of the early references for the further development of the strategy to better implement muqasah in the distribution of murabahah financing.